Respuesta :
a) The expression will be zero when x = -4 or 8
b) The trinomial equivalent of the expression is x² - 4x - 32
c) The trinomial equals to zero when x = 8
The given expression is (x - 8)(x + 4)
a) For what value of x will the expression be equal to zero
(x - 8)(x + 4) = 0
This can be split into:
x - 8 = 0
That is, x = 8
x + 4 = 0
That is, x = -4
The expression (x - 8)(x + 4) equals to zero when x = -4 or x = 8
b) Write this product as an equivalent trinomial.
A trinomial is a polynomial expression with three terms
Expand (x - 8)(x + 4)
x² + 4x - 8x - 32
x² - 4x - 32
c) Show that this trinomial is also equal to zero at the larger value of x from part (a)
The larger value of x from part (a) is 8
Substitute x = 8 into x² - 4x - 32
8² - 4(8) - 32
= 64 - 32 - 32
= 0
Learn more here: https://brainly.com/question/18718165